Examining Job Satisfaction Through Upward Influence Tactics Used by Employees Perceiving Organizational Politics - Frasat Kamran, Sarwat Sultan (Pakistan Journal of Psychology, 2014)
The present study was an attempt to explore the level of job satisfaction through upward influence tactics used by employees perceiving organizational politics. Participants were the 327 employees of 25 -49 years age, working in a manufacturing organization. All employees provided data on the questionnaires of perceived politics, upward influence tactics, and job satisfaction survey. On the basis of obtained scores on perceived politics, employees were grouped into two; 222 employees with perception of politics and 105 employees with no perception of politics. Employing descriptive and inferential statistics, results indicated the existence of high perception of organizational politics among employees. Findings suggested that employees perceiving politics used different upward influence tactics and were found with low job satisfaction than those who perceive no politics at their workplace. Findings also provided the significant main and interaction effects of perceived politics and influence tactics on job satisfaction.